Purification and Regulatory Properties of the Oxaloacetate Decarboxylase of Acetobacter xylinum - Benziman, Moshe (1978)
The oxaloacetate (OAA) decarboxylase (EC 4.1.1.3) activity of Acetobacter xylinum cells grown on glucose or glycerol is the same as that of cells grown on intermediates of the citrate cycle. The enzyme was purified 92-fold from extracts, and its molecular weight was determined to be 100,000 by gel filtration. Initial velocity studies revealed marked positive cooperativity for OAA (Hill coefficient [n(H)] = 1.8; S(0.5) = 21 mM). The affinity of the enzyme for OAA was markedly increased upon addition of nicotinamide adenine dinucleotide (NAD), NAD phosphate (NADP), and some other pyridine nucleotides. S(0.5(OAA)) decreased to 1 mM but n(H) and V(max) were unchanged. Saturation kinetics for the pyridine nucleotides were hyperbolic, and a half-maximal effect was obtained with 8 μM NAD and 30 μM NADP. The enzyme also catalyzed the exchange of (14)CO(2) into OAA but not the net carboxylation of pyruvate. Exchange activity, too, exhibited sigmoidal kinetics for OAA and was strongly stimulated by NAD at low substrate concentrations. The enzyme was inhibited by acetate competitively with respect to OAA. The K(I) for acetate (12 mM) was well within the physiological range of this compound inside the cell. The regulatory properties of the decarboxylase with respect to OAA cooperativity, NAD activation, and acetate inhibition were retained in situ within permeabilized cells. These properties seem to provide for a control mechanism which could insure the maintenance of OAA and the citrate cycle during growth of cells on glucose and, conversely, the required supply of pyruvate during growth on intermediates of the citrate cycle.